Impact of hypertension on changes in peripapillary retinal nerve fiber layer thickness in type 2 diabetes patients - Jae-Yun Sung; Tae-Seen Kang; Ka-Hyun Lee; Min-Woo Lee (Scientific Reports)
Abstract To determine longitudinal changes in the peripapillary retinal nerve fiber layer (pRNFL) thickness in type 2 diabetes mellitus (T2DM) patients with hypertension (HTN). Participants were divided into three groups: normal controls (Group 1), patients with T2DM (Group 2), and patients with both T2DM and HTN (Group 3). Following the initial examination, patients underwent three additional examinations at 1-year intervals. Linear mixed models were used to identify significant changes in pRNFL thickness over time. The baseline mean pRNFL thickness was 95.4 ± 7.9, 93.6 ± 7.8, and 90.7 ± 10.1 μm in Group 1, Group 2, and Group 3, respectively, (P = 0.046). The reduction rate for mean pRNFL thickness was − 0.15 μm/y in Group 1, – 0.54 μm/y in Group 2, and − 1.06 μm/y in Group 3, respectively (P = 0.026). In Group 2, T2DM duration (estimate = − 0.63, P = 0.002) was a significant factor associated with changes in pRNFL thickness in multivariate analysis. In Group 3, HTN duration (estimate = − 0.59, P = 0.036) and HbA1c levels (estimate = − 4.44, P = 0.019) were significantly associated with pRNFL changes. Under ischemic conditions caused by HTN, pRNFL damage due to diabetic retinal neurodegeneration is considered to be more severe. In such patients, the duration of ischemic damage caused by HTN appears to have a significant impact on pRNFL damage, and stricter blood glucose level control could help reduce pRNFL damage.